Health condition and risk attitude in the Dutch population: an exploratory approach. (19th May 2018) - Martín-Fernández, Jesús; Medina-Palomino, Hector J; Ariza-Cardiel, Gloria; Polentinos-Castro, Elena; Rutkowski, Anne
Abstract : Risk is a central aspect of health condition because attitudes towards risk may influence the inclination to adopt behaviours that can influence health condition. Taking preventive health care measures or purchasing a private health insurance are examples of decisions individuals make based on their preferences. This study analysed the relationship between health condition and behaviour under conditions of uncertainty and examined personal characteristics related to risk behaviour. Data was obtained from a survey on a representative sample of the Dutch adult population ( n  = 2, 822) conducted between May and June of 2014. Risk attitude was assessed through a self-reported scale and risk behaviours through a simulated lottery game, both included in the same survey. The relationship between risk attitudes and behaviours was examined, as well as certain socio-economic variables, including health condition, demographic characteristics, social status, and confidence in government institutions. Surveyed participants perceived themselves as risk-avoiding. However, their behaviour tended to be risk-seeking when playing lottery games, even when they faced potential (but limited) economic losses. Participants with poorer mental health condition tended to be less risk-inclined, which was not the case for participants who reported poor general health status. Participants feeling a higher satisfaction with their lives were willing to take greater risks in the lottery games. These findings allow for understanding risk behaviour as the interaction between personal perception of risk attitude and the assessment of risk associated to a specific situation. This assessment may be directly modulated by one's state of mind and not by physical health condition.